2010
DOI: 10.1007/s11248-010-9455-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of double repeated B subunit of Shiga toxin 2e at high levels in transgenic lettuce plants as vaccine material for porcine edema disease

Abstract: Pig edema disease is a bacterial disease caused by enterohemorrhagic Escherichia coli. E. coli produces Shiga toxin 2e (Stx2e), which is composed of one A subunit (Stx2eA) and five B subunits (Stx2eB). We previously reported production of Stx2eB in lettuce plants as a potential edible vaccine (Matsui et al. in Biosci Biotechnol Biochem 73:1628-1634, 2009). However, the accumulation level was very low, and it was necessary to improve expression of Stx2eB for potential use of this plant-based vaccine. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The HSP terminator from Arabidopsis thaliana has been demonstrated to increase the transcript of target transgenes in Arabidopsis, tobacco, rice, tomato, and lettuce (Hirai et al 2011;Kurokawa et al 2013;Matsui et al 2011;Nagaya et al 2010). In this study, we prepared two kinds of transgenic E. camaldulensis trees harboring CaMV 35S promoter-driven codA expression cassettes with different transcriptional terminators, i.e., the HSP terminator and NOS terminator ( Figure 1A) (NEDO 2013).…”
Section: Transcript Levels Of Coda In Transgenic E Camaldulensis Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSP terminator from Arabidopsis thaliana has been demonstrated to increase the transcript of target transgenes in Arabidopsis, tobacco, rice, tomato, and lettuce (Hirai et al 2011;Kurokawa et al 2013;Matsui et al 2011;Nagaya et al 2010). In this study, we prepared two kinds of transgenic E. camaldulensis trees harboring CaMV 35S promoter-driven codA expression cassettes with different transcriptional terminators, i.e., the HSP terminator and NOS terminator ( Figure 1A) (NEDO 2013).…”
Section: Transcript Levels Of Coda In Transgenic E Camaldulensis Treesmentioning
confidence: 99%
“…The heat shock protein (HSP) terminator derived from Arabidopsis thaliana has been demonstrated to increase both the transcription and translation of target transgenes in Arabidopsis, tobacco, rice, tomato, and lettuce (Hirai et al 2011;Kurokawa et al 2013;Matsui et al 2011;Nagaya et al 2010). Given this, we expected that the HSP terminator would enhance the transcription of exogenous abiotic stress-tolerance gene(s), and abiotic stress tolerance in Eucalyptus plantation trees.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the terminator derived from the Arabidopsis thaliana heat shock protein 18.2 gene (HSP, At5g59720) (HSPT) increases gene expression; the HSPT increases mRNA levels of both transiently and stably expressed transgenes approximately 2-fold more than widely-used NOS (nopaline synthase) terminator (Nagaya et al 2010). The HSPT is functional in a variety of plant cells including rice, A. thaliana, tomato, and lettuce (Hirai et al 2011;Matsui et al 2011;Nagaya et al 2010). In this study, with the goal of further increasing the expression level of transgenes, we evaluated a longer version of HSPT.…”
mentioning
confidence: 99%
“…To this end we performed transient expression analysis, in which naked DNA without chromosomal proteins serves as a template for transcription. Protoplasts were prepared form BY2 cells as described previously (Matsui et al 2011), and the Rluc-HSPT250 or the Rluc-HSPT878 was co-transfected with the expression plasmid for Fluc (AtADHFluc-HSPT250) for normalization of transfection efficiency. The Rluc/Fluc activity was calculated for each transfection, and average Rluc/Fluc activities of three fully independent transfections were determined relative to the activity obtained with HSPT250 ( Figure 3A).…”
mentioning
confidence: 99%
“…We have previously reported that active HRP was secreted into the culture medium from cells expressing the HRP gene without C-terminal vacuolar sorting signal (Matsui et al 2003), and that the expression level was increased by the use of NtADH 5′-UTR (Matsui et al 2006). is time, transcriptional terminator derived from A.thaliana heast shoch protein 18.2 gene (HSPT) was used to express HRP, because higher level expression of a transgene is possible using HSPT in various plant species including A. thaliana, lettuce, tomato, and rice (Nagaya et al 2010;Matsui et al 2011;Hirai et al 2011). Actually, we found that the HSPT is superior to a transcriptional terminator derived from Agrobacterium nopaline synthase gene (NOST) for expression of HRP in BY2 cells (Supplemental Figure 2).…”
mentioning
confidence: 99%